Abnormal Plasma Neuroactive Progestagen Derivatives in Ill, Neonatal Foals Presented to the Neonatal Intensive Care Unit. (9th September 2013) - Aleman, M.R.; Pickles, K.J.; Conley, A.J.; Standley, S.; Haggett, E.; Toth, B.; Madigan, J.E.
Abstract : Aims: To determine the pregnane profile of foals with neonatal maladjustment syndrome (NMS) and compare it with that of healthy controls and sick, non‐NMS foals. Methods: Thirty‐two foals with a clinical diagnosis of NMS, 12 foals with other neonatal disorders and 10 healthy control foals were selected for the study. Heparinised blood samples were collected from each group of foals and pregnane and androgen concentrations were determined using liquid chromatography mass spectrometry at 0, 24 and 48 h of age. Results: Healthy foals showed a significant decrease in pregnane concentrations over the first 48 h of life (P<0.01). Foals with NMS and sick, non‐NMS foals had significantly increased progesterone, pregnenolone, androstenedione dehydroepiandrosterone and epitestosterone concentrations compared with healthy foals (P<0.05). Progesterone and pregnenolone concentrations of sick, non‐NMS foals decreased significantly over 48 h (P<0.05), whereas concentrations in NMS foals remained elevated. Conclusions and practical relevance: Pregnane concentrations of ill, neonatal foals remain elevated following birth, reflective of a delayed, or interrupted, transition from intra‐ to extra‐uterine life. These pregnanes are potent allosteric modulators of the GABAA receptor and are important in providing tonic inhibition of fetal central nervous system activity and damping movement to prevent maternal damage. Infusion of the pregnane allopregnanolone into neonatal foals leads to somnolence and loss of affinity for the dam (Madigan et al .2012 ). Together, these findings suggest that the pathogenesis of NMS may be associated with the persistence of high concentrations of pregnanes. Serial progesterone and pregnenolone measurement may be useful in aiding diagnosis of NMS. Ethical animal research: The UC Davis IACUC approved the project.Sources of funding: Private donation.Competing interests: None.